If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -2u = 8u + 45 Reorder the terms: 12 + -2u = 45 + 8u Solving 12 + -2u = 45 + 8u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-8u' to each side of the equation. 12 + -2u + -8u = 45 + 8u + -8u Combine like terms: -2u + -8u = -10u 12 + -10u = 45 + 8u + -8u Combine like terms: 8u + -8u = 0 12 + -10u = 45 + 0 12 + -10u = 45 Add '-12' to each side of the equation. 12 + -12 + -10u = 45 + -12 Combine like terms: 12 + -12 = 0 0 + -10u = 45 + -12 -10u = 45 + -12 Combine like terms: 45 + -12 = 33 -10u = 33 Divide each side by '-10'. u = -3.3 Simplifying u = -3.3
| 124-3x=24+19 | | x/4+x+5/3=4 | | x-1/2x+x+3/4x=5/8 | | X^3-3x^2-x-3=0 | | 5/x+6=17/x | | x+2y+3z=1 | | 0.2y=3y | | 83-3x=10x+8 | | x=(8n+8n-1)2(4n-4n-1)2 | | 3p^4-8p^2+6=0 | | -5+11=14x-4-13x | | -15-(-31)=x/7 | | -6(t+1)=24 | | 20-14=3(x-2) | | b/7-18=-20 | | x+24+3x=-7-3x-11 | | c/8+3=7 | | 5x^2-10x^2=-7+x | | 42=30-m | | h/3+15=41 | | 4n-3=5n-5 | | -14x-20=12x+90 | | 76=58+9d | | 4(a-2)=16 | | (28y-1274)/2y=1 | | 2(y+2)=7 | | p-7=7 | | (2y-91)/2y=1/14 | | 2*14=21 | | 9v+17=-6 | | r/2-39=41 | | 2k-9=-15 |